Residual Characteristics and Dietary Risk Assessment of Dinotefuran and Tolfenpyrad in Tea Processing - LI Chunyong, LÜ Ying, JIN Jing, WANG Xia, QIN Shu (Shipin Kexue)
To clarify the residual characteristics of dinotefuran tolfenpyrad microemulsion during tea planting, drying and brewing, standardized field trials of pesticide registration residues were conducted in 10 provinces including Shandong and Zhejiang. Dietary risk assessment models were compared with and without adjustment of processing factors. The samples were extracted using acetonitrile containing 5% formic acid, salted out, purified by dispersed solid phase extraction, detected by ultra-high performance liquid chromatography-tandem mass spectrometry, and quantified by an external standard method. In the range of 0.005–0.500 µg/mL, a good linear relationship was obtained between the concentrations of dinotefuran and its metabolites as well as tolfenpyrad and their response peak areas (R2 > 0.99). The average recovery rates of dinotefuran and its metabolites 1-methyl-3-(tetrahydro-3-furylmethyl)guanidine (DN) and 1-methyl-3-(tetrahydro-3-furylmethyl)urea (UF) in fresh and dried tea leaves spiked at 0.05, 1.00, 20.00 and 50.00 mg/kg and in tea infusion spiked at 0.05, 0.10 and 5.00 mg/kg ranged from 74% to 103%, with relative standard deviations (RSDs) of 1%–9%. The spiked recovery rates of tolfenpyrad were between 75% and 95%, with RSDs of 1%–6%. The limit of quantitation (LOQ) was 0.05 mg/kg for all the analytes. In the case of the application of 20% dinotefuran·tolfenpyrad microemulsion at the recommended dose, both the national estimated daily intake (NEDI) for supervised trials median residue (STMR) adjusted with the drying factor of dinotefuran (containing its metabolites) in fresh tea leaves and that in dried tea leaves were 4.08 mg, accounting for 32.4% of the acceptable daily intake (ADI). The NEDI for STMR of tolfenpyrad adjusted with the drying factor in fresh tea leaves was 0.175 81 mg, accounting for 46.5% of the ADI, and the NEDI for STMR of tolfenpyrad in dried tea leaves was 0.189 25 mg, accounting for 50.1% of the ADI. According to different risk assessment models, the long-term exposure risk to both dinotefuran and tolfenpyrad was less than 100%. The national estimated short-term intake (IESTI) of dinotefuran (containing its metabolites) remained at the same risk level before and after processing factor adjustment, which was lower than the acute reference dose (ARfD) of 1 mg/kg. The IESTI of tolfenpyrad was 3.46 × 10-4 mg/kg, which was lower than the ARfD of 0.01 mg/kg, and tolfenpyrad residue was below the detectable level under the method established in this study, so no brewing facter and corresponding IESTI were obtained. In conclusion, the application of 20% dinotefuran·tolfenpyrad microemulsion on tea plants is safe at the recommended dose, and the risk of long-term and acute dietary exposure to dinotefuran and tolfenpyrad residues in tea is within the acceptable range. The risk assessment models with processing factor adjustment are closer to the actual risk level.